PENGGUNAAN MODEL INKUIRI TERBIMBING DENGAN PENDEKATAN JAS PADA MATERI USAHA DAN ENERGI - Ramadhan Aba; Treesje Katrina Londa Londa; Jeane Cornelda Rende (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
The use of learning models and approaches is important in the learning process. Physics learning needs to apply a learning model so that students can be actively involved in learning. Then they can construct their own knowledge that they learn through the investigation process. The guided inquiry model with the JAS approach is a learning model that can open up diverse thinking insights so that students can learn various concepts and how to relate them to natural phenomena. This study aims to determine the influence of the guided inquiry model with the JAS approach on learning outcomes and the learning environment on students' self-confidence in responding to learning. The method used in this research is experimental with the research design employed, namely, single group pretest-posttest (the one group, pretest-posttest design). The average score of learning outcomes using the guided inquiry model with the JAS approach (outside the classroom) was 74.14, and the average learning outcome using the guided inquiry model (inside the classroom) was 49.75. The results showed that the use of the JAS approach was very influential in understanding the concept of physics.